Overview of Building Codes and General Engineering Application - Racz, Richard (McGraw-Hill's AccessEngineering., 2023)
In this video we review the steps commonly required to determine the governing building code of a theoretical building project. Additionally, we discuss what the IBC is, how it came to be, and where it has been adopted within the U.S.